Penser la force politique des voix trans et féministes en musique - Liz Escalle-Dyachenko (Glad!)
This article aims to think about the political force of trans and feminist voices in music, drawing on the epistemological tools of feminist music criticism and trans studies. Its goal is to examine, from a situated knowledge perspective, how trans vocal practices can achieve to produce and represent feminist positions and politics that encourage body autonomy and emancipation. My theoretical proposal is built around three steps: first, I articulate a methodology for the study of trans voices which centers their sonic agency against cissexist erasures and violence. Then, I describe how these voices are grounded in minoritarian and/or oppositional archives of the present, prompting the emergence of what I call a tiers-archive. I argue that this sensitive infrastructure sustains the historical, local, and plural materialization of trans voices in the field of music as well as in the field of trans and feminist struggles. Finally, I examine how these voices can also generate the conditions for a transfeminist listening. This listening enables the making and embodiment of common practices, not only for the musicians and artists, but also for their public.